WORD-FORMATION FEATURES OF NEOLOGISMS IN MODERN ENGLISH - Загурська, Галина (SWorldJournal, 2025)
This article focuses on types of neologisms in modern English language and their word formation processes. The aim of the article is to analyse neologisms of the banking section representing the universal concept of time as lexical units having identified